Var Grundtvigs nadversyn luthersk? - Thodberg, Christian (Grundtvig-studier, 1975)
Was Grundtvig’s Eucharist Lutheran?By Christian Thodberg This question is examined through an analysis of Grundtvig’s attitude to, in particular, the various elements of the sacrament. In 1806 Grundtvig’s view was undoubtedly a reformed one; the divine is too exalted to be contained in earthly things - a romantic viewpoint - and Grundtvig thus maintained a symbolic interpretation of the Eucharist.When Grundtvig in later years described himself as Lutheran, he was not following Luther’s interpretation of the Eucharist, namely, that Christ is present in substance in the bread and the wine. Nevertheless, Grundtvig did accept a real presence, cf Nugent Wade, the English chaplain at the legation, who reported Grundtvig’s position thus: » He is positive upon a real presence - takes that to be the word which he says is a body and considers the words of Christ in sacrament to be his bodily presence«. Grundtvig considers the words of institution and in particular the commandment - » Take this ana eat it — all of you drink from this - do this in remembrance of me« to be bearers, in concentrated form, of Christ’s presence at the Eucharist. From this Grundtvig formulates an interpretation of the Eucharist which reminds one of the Johannine Eucharist of the Early Church, with its emphasis on fellowship, meal, praise and a premature celebration of eschatological bliss. Where Grundtvig links the real presence to an objective fact he is obviously inspired by Luther, but he differs from Luther in laying greater stress on the words of institution rather than the bread and wine.